(untitled) (Research, Society and Development, 2023)
Otosclerosis is a disease related to inflammatory otodystrophy, the cause of which is still not very clear, being associated with a change in the histological component, in particular the structures of the otic capsule and ossicular chain. It is a pathology with a hereditary component, autosomal dominant and low penetrance, which mainly affects the temporal bone. It is the most common reason for hearing loss in young adults, being more associated with women, in a ratio of 2:1. This pathology mostly affects the Caucasian population, being rarely found in the Asian and African-American population. It is found on average between the second and fourth decade of life. Due to the lack of studies on otosclerosis, this article aims to bring together the main findings found in the literature for a better understanding of this disease, such as etiopathogenic aspects, imaging findings and associated therapeutic modalities. This article is a narrative review of the literature, with searches carried out based on the Pubmed, Virtual Health Library, Scielo and Google academic platforms, using the keywords: Otosclerosys, otosclerosis and treatment and otosclerosis and diagnosis, during the months April and May 2023. Multidetector computed tomography (MDCT) is an ally in the study of otosclerosis, as it helps in the search for the location and characterization of the lesion, confirmation of diagnosis and surgical planning, in addition to providing opportunities for differential diagnosis. Thus, many studies about this pathology are necessary, in view of the clinical repercussions involved.